IOTA-Next Generation Block chain - M, Divya; Biradar, Nagaveni B. (International Journal of Engineering and Computer Science, 2018)
IOTA is a revolutionary new, next generation public distributed ledger that utilizes a novel invention, called a “Tangle”, at its core. The Tangle is a new data structure based on a Directed Acyclic Graph (DAG). As such it has no Blocks, no Chain and also no Miners. Because of this radical new architecture, things in IOTA work quite differently compared to other Blockchains.